2021
DOI: 10.1186/s12882-020-02218-5
|View full text |Cite|
|
Sign up to set email alerts
|

Hemolytic uremic syndrome caused by sea anemone sting: a case report

Abstract: Background Some sea anemone toxins cause renal injuries resembling hemolytic uremic syndrome (HUS). To date, only a few cases of HUS caused by sea anemone stings have been reported. In this case report, we have described an HUS case caused by a sea anemone sting. Case presentation In November 2019, a 37-year-old man with no underlying disease was admitted to our hospital. He presented with intense pain, a rash on, and swelling in his right thigh. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…6 There are few reports of patients seeking hospitals on the day of injury, and most patients seem to consult doctors in urban areas who are relatively unfamiliar to tropical medicine, therefore, making it difficult to establish an accurate diagnosis. 3,4 The organism also changes its appearance in a variety of ways to suit its surroundings. 6 Therefore, information on the shape of what it touches is not always useful.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…6 There are few reports of patients seeking hospitals on the day of injury, and most patients seem to consult doctors in urban areas who are relatively unfamiliar to tropical medicine, therefore, making it difficult to establish an accurate diagnosis. 3,4 The organism also changes its appearance in a variety of ways to suit its surroundings. 6 Therefore, information on the shape of what it touches is not always useful.…”
mentioning
confidence: 99%
“…1 Although the great majority of sea anemones is similarly harmless, contact with Phyllodiscus semoni, which lives in the Central Indo-West Pacific to the East China Sea, not only causes a localized skin eruption but also renal failure. [2][3][4] In some cases, dialysis treatment has been required. 4 We report a case of sea anemone dermatitis associated with acute renal failure caused by Phyllodiscus semoni.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors identified an error in the affiliation of author Jun Young Do and author Min Kyoung Kim.…”
mentioning
confidence: 99%